Thymoquinone is protective against 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin induced hepatotoxicity. (18th August 2018) - Erdemli, ME; Yigitcan, B; Gul, M; Bag, HG; Gul, S; Aksungur, Z
Abstract: We investigated changes in rat liver tissues following administration of thymoquinone (TQ) against 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin (TCDD) induced hepatotoxicity. Fifty rats were assigned randomly to five groups of 10 as follows: control, corn oil, TCDD, TQ and TCDD + TQ. Biochemical and histopathological analyses were conducted on liver tissue. We found that 30 day TCDD administration caused histopathological changes in liver including thickening of Glisson's capsule, intracytoplasmic vacuolization in hepatocytes, sinusoidal dilation, vascular and sinusoidal congestion and inflammatory cell infiltration. TCDD administration increased malondialdehyde (MDA), total oxidant status (TOS), alanine aminotransferase (ALT), aspartate aminotransferase (AST) and alkaline phosphatase (ALP) levels in rat liver tissue and reduced glutathione (GSH), superoxide dismutase (SOD), catalase (CAT) and total antioxidant status (TAS) levels compared to all other groups. In the TQ treated group, GSH, SOD, CAT and TAS levels increased compared to all other groups. MDA, TOS, ALT, AST, ALP levels decreased compared to all other groups. Our histological findings were consistent with the biochemical findings. The oxidative and histologic effects of TCDD were eliminated by TQ treatment. TCDD administration caused oxidative stress in rat liver and TQ administered with TCDD prevented TCDD induced hepatotoxicity. TQ could be considered an alternative anti-TCDD toxicity agent.